Analisis Kebijakan Pelarangan Sepeda Motor Melintas Pada Jalan MH Thamrin - Medan Merdeka Barat Di DKI Jakarta - Satya Pranata (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
The growth rate of vehicles in Jakarta, motorcycles are vehicles with the highest growth rate compared to other vehicles, so that in order to overcome the level of congestion it is necessary to have a policy that regulates the flow of these two-wheeled vehicles. In 2014, the Governor of DKI Jakarta issued Regulation of the Governor of DKI Jakarta Number 195 of 2014 concerning Restrictions on Motorcycle Traffic, which among other things contained rules for prohibiting motorcycles from crossing at MH Thamrin-Medan Merdeka Barat aimed at reducing congestion, pollution and accident rates. However, this policy was finally revoked by the Supreme Court through decision number 57 P/HUM/2017 which was published on November 21, 2017. The case example can be reviewed through analysis based on public policy theory to determine the impact of the policy using 3 (three) theories, namely: analysis based on public policy theory, analysis based on policy systems and analysis based on the main forms of public policy analysis which concluded that the Policy for the Prohibition of Motorcycles Crossing on Jalan MH Thamrin-Medan Merdeka Barat arose as a result of congestion levels and high accident rates as a result of The number of motorcycles is increasing every year. The problem that arises in this policy is that the benefits of this policy are not evenly distributed, meaning that not all people feel benefited from this policy, especially motorcycle riders who feel very disadvantaged due to the implementation of this policy.